Implementación de una guía virtual para smartphones android mediante códigos qr utilizando la metodología mobile-d para enriquecer la interacción del visitante con la proyección del patrimonio histórico, cultural y social del museo de la escuela fiscal Isidro Ayora en el período de julio 2015 - enero 2016 - Carrillo Betancourt, Josselin Karina (2016)
The ‘Isidro Ayora’ School Museum located in Latacunga Canton on Quijano y Ordoñez and Tarqui streets is open to citizens of all ages. It shows all its art supplies which are exhibited in a traditional, monotonous, and unremarkable way. That why the museum is not very frequented by visitors. Therefore, it does not allow the development and recognition of the Museum. For this research development, the hypothetical-deductive and analytical methods were used. In addition, through the implementation of surveys to teachers, school seniors and people in general. Furthermore, interviews were made to the authorities, they establish that the Museum does not have technological alternatives to show the historic, cultural, and social patrimony, showing in this way that a virtual guide is a technological solution to promote the visit to this museum and of course its diffusion as well as, the implementation of new technologies help change a forgotten environment in an interactive and friendly place. With the implementation of a Virtual Guide at ‘Isidro Ayora’ School Museum, people who visit it can interact with the art supplies which exhibit and show all the information in any Android mechanism by only scanning the QR code and this will allow the innovation, diffusion and recognition of this Museum.